2005
DOI: 10.1271/bbb.69.2368
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of an Ellagic Acid-Rich Pomegranate Extract on Tyrosinase Activity and Ultraviolet-Induced Pigmentation

Abstract: A pomegranate extract (PE) from the rind containing 90% ellagic acid was tested for its skin-whitening effect. PE showed inhibitory activity against mushroom tyrosinase in vitro, and the inhibition by the extract was comparable to that of arbutin, which is a known whitening agent. PE, when administered orally, also inhibited UV-induced skin pigmentation on the back of brownish guinea pigs. The intensity of the skin-whitening effect was similar between guinea pigs fed with PE and those fed with L-ascorbic acid.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
1
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(131 citation statements)
references
References 24 publications
2
123
1
5
Order By: Relevance
“…Tyrosinase inhibitory effect was further evaluated 20 . Tyrosine is the starting material for the production of melanin pigment, the brown-black eumelanin and the yellow-red pheomelanin.…”
Section: Resultsmentioning
confidence: 99%
“…Tyrosinase inhibitory effect was further evaluated 20 . Tyrosine is the starting material for the production of melanin pigment, the brown-black eumelanin and the yellow-red pheomelanin.…”
Section: Resultsmentioning
confidence: 99%
“…It was also reported that 3,3 -di-O-methyl ellagic acid is present in the bark extract of S. alba 22 . The rind extract of pomegranate, which is rich in ellagic acid, exhibited inhibitory activity against mushroom tyrosinase in vitro 23 . The effect was even comparable to that of arbutin, a known hypopigmenting agent.…”
Section: Resultsmentioning
confidence: 99%
“…14,15) Although we could also find sulforaphane with the usual method by measuring the melanin content using B16 melanoma cells, 5) this method took a long time and was troublesome for high-throughput screening. We developed in this study a new and more effective screening method to search for skin-whitening agents.…”
Section: Discussionmentioning
confidence: 99%